ANALISIS MODEL SPEECH ACTS DOSEN DI LIHAT DARI GENDER PERSPECTIVE DALAM PEMBEJARAN BAHASA INGGRIS DI JURUSAN ADMINISTRASI NIAGA - Hindri Febri Ana Sari; Laura S. Nunumete; M. Rizkoni Salis , (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Language used has to specific function whereas a number of students are not aware with the function. In fact, the problem recurrently happens in classroom when the lecturers mean is changed from what they have been stated. In order to diminish the misinterpretation of language used uttered both man and woman lecturers, the model of speech acts is powerfully essential to be formed based on the gender perspective as the purpose of the research. Researcher clearly used descriptive research with purposive sampling. The data of this research were the English lecturers’ utterances used both man and woman in the classrooms. The results of the research were QEC(Questioning, Explaining, Commanding) pattern regularly expressed by woman (16 categories with total 489) and CQE (Commanding, Questioning, Explaining) pattern generally accomplished by the man lecturer (9 categories with total 121). To sum up, both of the speech acts patterns performed in teaching are properly qualified to be applied in the meantime the teaching strategy focuses on students’ center.